A Review of the Pharmacist as Vaccinator - Willis M. Richardson; Albert I Wertheimer (University of Minnesota Libraries Publishing, 2019)
Objective: The aim of this study is to review literature about how the pharmacist's role as vaccination providers has been financially and clinically measured. Methods: A broad literature search was conducted up to May 2016 to identify economic or clinical data on pharmacy vaccinations. MEDLINE® and PUBMED databases were searched for publications useful or potentially useful for this review. The NIH and CDC websites were also searched for relevant materials. Search terms included vaccination, pharmacist, economic, pharmacoeconomics, cost, benefits cost-effectiveness, physicians, immunizations, vaccinations, pharmacy vaccines, cost, physician vaccines, financial, benefit, ambulatory pharmacist vaccination, clinical pharmacist, economics, pharmacist vaccine impact. Results: The search yielded a total of 68 articles of which 12 met the criteria to be included in this review. After examining articles for relevance to pharmacy vaccinations, two tables were created to highlight the clinical and economic advantages of the pharmacist as a vaccinator. Conclusion: Pharmacists who administer vaccines are an underutilized provider. This literature review reveals a pattern among studies measuring the pharmacist's impact on vaccination rates, patient preferences, and cost savings. Pharmacists have a history of demonstrated dependability, accuracy, and cost effectiveness. State laws, collaborative agreements, and health plans have continued to prevent patients from using the pharmacy to receive the CDC recommended vaccines. These barriers ultimately delay the Healthy People 2020 goals.   Article Type: Review